Ranmor Mutation Management to Improve the Quality of Public Services to Realize Precision Police at Kudus Police - Wibowo, Imam Eko Akbar Yudha (Indonesian Journal of Police Studies, 2024)
Kudus Police Traffic Unit data from 2021 to September 2022 shows the high number of Ranmor mutations in Kudus Regency. Problem with Ranmor mutation process because the time is unclear, the mechanism is long and is considered complicated by taxpayers and must prepare quite large administrative costs. Method A qualitative approach and filed research type of research were used in this research. Primary and secondary data sources were taken using data collection techniques interviews, observations, and document review. In addition, data validity is required and interactive model analysis techniques. Use of management theory as an analytical tool which consists of management elements and functions. The research results conclude The management of Ranmor transfers at the Kudus Police has not yet met the service requirements public and the provisions of Regident Ranmor due to inconsistencies in the Source Organizational Power (SDO) and the system and methods of the Kudus Police Traffic Police Traffic Unit. From these problems, problem solving steps reflect ideal conditions and efforts to improve public services oriented towards the concept of "Precision Police" so that realizing quality service.